2004
DOI: 10.1002/jbm.b.30129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of fluoride‐containing acetic acid on NiTi wires

Abstract: The possibility of the formation of hydrofluoric acid by the reaction of fluoride with acetic acid seems natural in the oral cavity. The effect of an acidic fluoride solution on NiTi wires was investigated by testing microhardness and color changes on wires. For aesthetic reasons, the color change on wires was also evaluated. Wires were immersed in four different test solutions for 1 or 3 days. As-received wires were used as a reference. After immersion for 3 days, the microhardness of the tested wires increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
9
0
3
Order By: Relevance
“…Ni–Ti superelastic alloy is widely used in dental devices, such as orthodontic wires, because of its superior mechanical properties, good corrosion resistance, and biocompatibility. However, in the presence of fluoride, this alloy undergoes a marked corrosion 1–6. Fluoride, such as NaF, is contained in toothpastes, prophylactic agents, and dental rinses, because fluoride has a cariostatic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Ni–Ti superelastic alloy is widely used in dental devices, such as orthodontic wires, because of its superior mechanical properties, good corrosion resistance, and biocompatibility. However, in the presence of fluoride, this alloy undergoes a marked corrosion 1–6. Fluoride, such as NaF, is contained in toothpastes, prophylactic agents, and dental rinses, because fluoride has a cariostatic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, the surface should show some pores or some visible modification. According to our previous study, wires immersed in HF-formed (greater than 10 ppm) acidic fluoride solution showed enhanced microhardness and pores after immersion 25) .…”
Section: Discussionmentioning
confidence: 76%
“…Further, HF concentration limit can be changed according to the acid added to adjust the pH value, because each acid has a different acidity. According to our previous study, wires immersed in acidic NaF solutions were full of micropores and the severity depended on the concentration of HF 25) . However, in the present study, no surface modification was found regardless of wire type and contacting resin product.…”
Section: Discussionmentioning
confidence: 98%
“…Intraoral structures are exposed to an ever-changing environment including saliva, foods, bacteria and their product. Protein in food and digestive enzymes make the saliva not only a single phosphate buffer, but a complex system containing protein 6,7. Limited studies on corrosion behavior of alloys have been reported in protein-containing solutions.…”
Section: Introductionmentioning
confidence: 99%